Recurrent Public Health Care Sector Strikes in Nigeria: Understanding the Causes and Taming the Tide - Usar, I. J.; Akosu, J. I.; Okoye, C. (British Journal of Healthcare and Medical Research, 2022)
Nigeria is one of the unhealthiest countries in sub-Saharan Africa due in part to the chronic human resource for health challenges of inadequate critical health professionals, inappropriate skill mix, mal-distribution and persistent emigration of highly skilled health professionals. Since the advent of democracy in 1999, the country has been thrown into cycles of crippling heath workforce strike actions in the public health care sector. A number of interventions by governments have failed to stem the tide of strikes. The study examines why the rampant nature of these strikes and recommend actionable strategies to mitigating their frequency. The study adopted a mix method approach to collect quantitative and qualitative data, using questionnaires and key informant interviews. Qualitative interviews were analysed by content analysis and interpretation, and descriptive statistics applied to quantitative information. We established that epidemic of strikes crippling public health facilities have multiple origins, which range from agitations for improved welfare, inter-professional health leadership rivalries, conflicting professional regulatory policies and a lack of honest collective bargaining with unions and political will to faithfully implement agreements. To halt the slow, but steady slide of the public health care into a state of collapse, government must let go its current fragmented approach to resolving industrial disputes in the public health sector for multi-prong strategy that recognizes the interrelationships in the health terrain.